Evaluating Sustainability:: Limits and Possibilities in Alto Douro Vinhateiro, Portugal (Sustainability in Debate, 2013)
The Alto Douro Wine Region, located in North of Portugal, is one of the most important portuguesewine regions. In last decades, it has faced serious difficulties, common to many rural areas of thecountry and around the world. Problems such as aging and population loss, low economic, socialand cultural density, low literacy, difficulties in the wine sector, poor associative movement, lackof common strategies among regional municipalities, and institutional difficulties, among others,affect its development and suggest that the region may not be managed in a sustainable way.Facing this scenario, a methodology to assess regional sustainability was developed. 76 indicatorswere used, grouped into 23 aspects and 5 dimensions. From this evaluation, a regional value wasobtained which translates the regional situation relating to sustainable development. In a 0 to100 scale, the region received a score of 57.14 points, showing that sustainability, if implementedas a regional strategy, could be highly benefic to regional improvement.